HEALTHCARE DECISION SUPPORT SYSTEM EVOLUTION: IMPACT TO SOCIAL GOVERNANCE - Normadiah Mahiddin; Nur Arzuar Abdul Rahim; Noraini binti Mohamed; Zulkifli Halim (Journal of Islamic, Social, Economics and Development, 2024)
Good health is a highly important asset in the lives of individuals; hence healthcare is a pivotal factor in determining the overall quality of life. Due to its complexity, healthcare encompasses various dimensions, with decision-making standing out as a critical aspect. Currently, the healthcare system is categorized into five stages, namely primary care, secondary care, tertiary care, quaternary care, and palliative care. The evolution of the decision-support system has contributed to the integration and advancement of these five healthcare stages. Through a comprehensive approach involving a literature study, healthcare document analysis, and domain expert interviews, this study utilizes diabetes as a case study to understand the healthcare nature and the healthcare system. Thus, this paper reviews the HDSS evolution and its impact on the healthcare system's development, providing practical insight into the overall healthcare system based on healthcare decision-making. The findings reveal a significant transformation in the healthcare system over time. In conclusion, this study sheds light on healthcare decision-making issues and how it evolves around the healthcare system, driven by the adoption and advancement of the Healthcare Decision-Support System. The insights gained from this research will guide future endeavors in enhancing healthcare delivery and decision-making processes.